Time-varying associations between loneliness and physical activity: Evidence from repeated daily life assessments in an adult lifespan sample - Broen, Tiana; Choi, Yoonseok; Zambrano Garza, Elizabeth; Pauly, Theresa; Gerstorf, Denis; Hoppmann, Christiane A. (Frontiers in Psychology, 2023)
Physical activity is a behavior that promotes physical and mental health; yet physical activity has decreased during the COVID-19 pandemic. To promote health during times of challenge, it is important to identify potential barriers to this key health behavior, such as loneliness. This brief report extends previous research on physical activity and loneliness that mainly focused on between-person differences to examine their time-varying associations at the within-person level using repeated daily life assessments. From April 2020 to August 2020, data were collected from a sample of 139 community-dwelling Canadian adults (Mage = 40.65 years, SD= 18.37; range= 18-83 years). Each evening for 10 consecutive days, participants reported their loneliness, number of steps, and minutes of moderate-to-vigorous physical activity. Results revealed that, in line with our hypotheses, on days when participants reported more loneliness they also engaged in less moderate-to-vigorous physical activity than on less lonely days (estimate = –0.23, p = .01); there was a trend in the same direction for daily steps at the within-person level (estimate = –16.98, p = .052). In contrast, at the between-person level, overall loneliness was not associated with overall physical activity engagement after accounting for within-person differences and control variables (age, sex, day in study). From an intervention perspective, our findings suggest that it is promising to tackle loneliness on a day-to-day basis to increase physical activity one day at a time. This may be especially relevant during times mandating social-distancing, but also at other times when individuals experience greater feelings of loneliness.